(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The progress achieved in the areas of improving processing methods, the introduction of bent and glued wood, and the use of biofire protection products have opened up new reserves of this material. The use of wood, especially valuable species, has helped to reveal the multifaceted beauty of modern aesthetic and constructive solutions. Projects implemented in the world convincingly demonstrate the possibility of forming unique comfortable spaces in budget financing conditions. Taking this into account, it is natural to use natural materials and natural landscaping as the most economical and comfortable solutions. Wood is associated with "warm" sensations during visual and tactile contact - optical perception of the pattern of fibers activates the imagination, touching the structure of the wood surface has a beneficial and calming effect on the emotional state of a person. The main disadvantages of wood processing on CNC machines include significant capital investments in equipment, the need to use expensive software products, a significant duration of finishing, the complexity of creating a three-dimensional model, and the lack of product exclusivity. The use of 3D technologies in combination with traditional materials opens up opportunities for reducing production costs. One of the main tasks with which the introduction of the new technology will be the development and modernization of existing and current technologies for the production and manufacture of wood materials and products, so that they can be adapted or supplemented for 3D printing. It is necessary to combine the development of wood materials, advanced robotics and additive manufacturing processes, not to mention the development of new tools that will help them develop sustainable wood-based composites that will be suitable for the production of medium- and large-scale 3D printing. Further development of this technology will allow the use of traditional materials more rationally, including secondary resources and renewable sources, which will lead to a reduction in the cost of projects.